Filosofia como iniciação e a técnica do logos no Fédon - Souza, Eliane Christina (Revista Archai, 2015)
Abstract: Knowledge, characterized in the initial section of the Phaedo as possessing the forms by the soul, is unattainable under special conditions: a pure soul can only find the pure beings after death and, for this to happen, it is necessary that the genuine philosopher engages in philosophy as an initiation. However, in the final section of the dialogue, the work with the logoi and the hypothesis seems to constitute a more dynamic form of philosophy. I propose to examine the relation between the initial part of the dialogue, in which knowledge obtained by the soul in fully favourable conditions is associated to the mysteries, and the final section, which presents the technique of discourse as a possibility of knowledge for the man in their condition of mixture body and soul. Keywords: Philosophy, knowledge, discourse.